The disgusting sandwich - Edwards, Gareth; Shaw, Hannah (Scottish book trust UK, 2016)
One day, a boy drops his sandwich in a sandpit, and the race is on! A very hungry badger wants it, but he's just not quick enough. The sandwich is dropped, squashed and slithered over by everyone from a squirrel, to a fox, to a band of slugs. Will the badger ever get his paws on that sandwich?